DEVELOPMENT OF INFORMATION COMPETENCE OF FUTURE TEACHERS ON THE BASIS OF AN INTEGRATIVE APPROACH - Ganiyeva O.S. (International Scientific and Current Research Conferences, 2023)
The article presents ideas about the pedagogical foundations of the development of information competence of future teachers. Information competence in pedagogic subjects, information competence of students of higher educational institutions of pedagogy is aimed at professional development.